Review of the leucotela species-group of Conura (Hymenoptera: Chalcididae) from Amazon rainforest - de Aguiar Brotto, Thales Renan; Tavares, Marcelo Teixeira (Zootaxa, 2021)
The leucotela species-group of Conura Spinola (Hymenoptera: Chalcididae) was initially proposed to include C. leucotela (Walker 1862) within the subgenus Spilochalcis Thomson. Despite this treatment, the accurate identification of C. leucotela is not possible based on the literature. In this paper, C. leucotela is redescribed and two new species, C. paraleucotela sp. nov. and C. pseudoleucotela sp. nov., are described within the leucotela group, with all the species based on female singletons. Additionally, diagnoses and illustrations are presented for two other unnamed species based on males. The taxonomic concept of the species group is discussed, and new diagnostic characters are proposed. An identification key and illustration of species are provided. The morphology of the coupling mechanism of the propodeum and gaster of some species of the leucotela group and its relation with possible hosts is discussed. A short discussion of rarity of the leucotela group is presented.